Stress-induced translation of KCNB1 contributes to the enhanced synaptic transmission of the lateral habenula - Ryu, Hakyun; Kim, Minseok; Park, Hoyong; Choi, Han Kyoung; Chung, ChiHye (Frontiers in Cellular Neuroscience, 2023)
The lateral habenula (LHb) is a well-established brain region involved in depressive disorders. Synaptic transmission of the LHb neurons is known to be enhanced by stress exposure; however, little is known about genetic modulators within the LHb that respond to stress. Using recently developed molecular profiling methods by phosphorylated ribosome capture, we obtained transcriptome profiles of stress responsive LHb neurons during acute physical stress. Among such genes, we found that KCNB1 (Kv2.1 channel), a delayed rectifier and voltage-gated potassium channel, exhibited increased expression following acute stress exposure. To determine the roles of KCNB1 on LHb neurons during stress, we injected short hairpin RNA (shRNA) against the kcnb1 gene to block its expression prior to stress exposure. We observed that the knockdown of KCNB1 altered the basal firing pattern of LHb neurons. Although KCNB1 blockade did not rescue despair-like behaviors in acute learned helplessness (aLH) animals, we found that KCNB1 knockdown prevented the enhancement of synaptic strength in LHb neuron after stress exposure. This study suggests that KCNB1 may contribute to shape stress responses by regulating basal firing patterns and neurotransmission intensity of LHb neurons.